2004
DOI: 10.1101/gad.303504
|View full text |Cite
|
Sign up to set email alerts
|

The mouse homeobox gene Not is required for caudal notochord development and affected by the truncate mutation

Abstract: The floating head (flh) gene in zebrafish encodes a homeodomain protein, which is essential for notochord formation along the entire body axis. flh orthologs, termed Not genes, have been isolated from chick and Xenopus, but no mammalian ortholog has yet been identified. Truncate (tc) is an autosomal recessive mutation in mouse that specifically disrupts the development of the caudal notochord. Here, we demonstrate that truncate arose by a mutation in the mouse Not gene. The truncate allele (Not , and Not tc/tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
135
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(145 citation statements)
references
References 57 publications
10
135
0
Order By: Relevance
“…Decrease in the number of homozygotes born versus the number expected was already reported in similar studies. Moreover, detection of the homozygotes with normal tail morphology was in accordance with the previously reported variable severity of the Noto tc phenotype [9,11]. Theoretical possibility that the homozygote would be recognized as a heterozygote did not occur, as the mice without a tail were never recognized as heterozygotes.…”
Section: Reliability Of Splotch (Pax3 Sp ) and Truncate (Noto Tc ) Stsupporting
confidence: 70%
See 1 more Smart Citation
“…Decrease in the number of homozygotes born versus the number expected was already reported in similar studies. Moreover, detection of the homozygotes with normal tail morphology was in accordance with the previously reported variable severity of the Noto tc phenotype [9,11]. Theoretical possibility that the homozygote would be recognized as a heterozygote did not occur, as the mice without a tail were never recognized as heterozygotes.…”
Section: Reliability Of Splotch (Pax3 Sp ) and Truncate (Noto Tc ) Stsupporting
confidence: 70%
“…Two representative mouse lines were tested: splotch, Pax3 mutant (Pax3 sp ) which carried a short deletion/insertion of 6 bp (Pax3:c.456-7T_-2AdelinsCGTGTG) [8] and truncate, Noto mutant (Noto tc ), which carried a SNS (Noto:c.503T>G) [9]. Splotch homozygous embryos often die due to heart and neural tube defects.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This complex functions as a general transcription regulation complex and is ubiquitously expressed. Abdelkhalek et al 12 showed that in mouse embryos loss of the ortholog Not results in abnormal notochord formation in and caudal to the posterior trunk.…”
Section: Discussionmentioning
confidence: 99%
“…The primary embryonic organizer, Spemann's organizer in the amphibian embryo, Hensen's node in rabbit and mouse, and the embryonic shield in the teleost fish embryo, from which the dorsal forerunner cells and hence Kupffer's vesicle (KV) are derived, thus sets the stage for the development of the PNC/GRP/KV or its equivalent in other vertebrates, which func-tionally may turn out to be primarily involved in LR axis development. Experimental manipulation of the organizer thus affects all three body axes, while defects in PNC/GRP/KV cause laterality defects without affecting the main body axes (Herrmann and Kispert, 1994;Nonaka et al, 1998;Krebs et al, 2003;Przemeck et al, 2003;Abdelkhalek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%